Linarin ameliorates innate inflammatory response in an experimental dry eye model via modulation of the NLRP3 inflammasome - Chen Mei; Li Jie; Peng Jun; Huang Yu; Ouyang Weijie; Liu Xiaoqing; Shen Zhibin; Li Changdong; Wang Yi; Peng Qinghua (KeAi Communications Co., Ltd., 2021)
Objective: To investigate the effect and mechanism of linarin (LA) in an experimental dry eye model Methods: LA or vehicle was applied in two dry eye models: an in vitro hyperosmotic stress model and an in vivo desiccating stress (DS) murine model. The viability of human corneal epithelial cells (HCECs) was measured using a cell counting kit (CCK-8). Tear secretion was assessed using the phenol red cotton test. The tear break-up time (TBUT) was recorded using 0.1% liquid fluorescein sodium. Corneal epithelial permeability was evaluated through Oregon green dextran (OGD) staining. Conjunctival goblet cells were counted using periodic acid-Schiff (PAS) staining. Terminal deoxynucleotidyl transfer dUTP nick-end labeling (TUNEL) staining was used to quantify apoptotic cells in both models. The expression of Ki-67 was measured in HCECs in the cell model while that of matrix metalloproteinase (MMP)-3 and -9 was measured in the murine model through immunofluorescence staining. Real-time quantitative PCR (RT-qPCR) was performed to assess the expression of MMP-3 and MMP-9 in the corneal epithelium and NLRP3, ASC, Caspase-1, interleukin (IL)-1β, IL-18, and tumor necrosis factor (TNF)-α in the conjunctiva. The protein expression levels of NLRP3, ASC, Caspase-1, IL-1β, and IL-18 in the conjunctiva were assessed via Western blot Results: In the in vitro model, treatment of HCECs with LA showed no toxicity, increased proliferation, and reduced apoptosis. In the murine model, compared to the control, LA significantly increased tear production and TBUT, improved OGD staining, and increased the number of goblet cells. Topical treatment of LA to mice provided decreased expression of MMP-3, MMP-9, TNF-α, and apoptotic corneal epithelium. Topical administration of LA also suppressed the NLRP3 inflammasome in the dry eye disease (DED) murine model by decreasing the expression of NLRP3, ASC, Caspase-1, IL-1β, and IL-18 in the conjunctiva. Conclusion: Our findings support the safety and efficacy of LA in the treatment of DED. LA alleviated corneal epithelial damage and suppressed NLRP3 inflammasome-mediated immunity in the conjunctiva in a murine model of DED.